2020
DOI: 10.1136/neurintsurg-2020-016349
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and neurointerventional service worldwide: a survey of the European Society of Minimally Invasive Neurological Therapy (ESMINT), the Society of NeuroInterventional Surgery (SNIS), the Sociedad Iberolatinoamericana de Neuroradiologia Diagnostica y Terapeutica (SILAN), the Society of Vascular and Interventional Neurology (SVIN), and the World Federation of Interventional and Therapeutic Neuroradiology (WFITN)

Abstract: BackgroundThis survey was focused on the provision of neurointerventional services, the current practices of managing patients under COVID-19 conditions, and the expectations for the future.MethodsInvitations for this survey were sent out as a collaborative effort of the European Society of Minimally Invasive Neurological Therapy (ESMINT), the Society of NeuroInterventional Surgery (SNIS), the Sociedad Iberolatinoamericana de Neuroradiologia Diagnostica y Terapeutica (SILAN), the Society of Vascular and Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 9 publications
0
19
0
2
Order By: Relevance
“…Fiehler et al. 19 reported the results from an international survey, demonstrating a significant decrease in emergent neurointerventional volume reported by 69% of the responders. We did not find such a decrease in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fiehler et al. 19 reported the results from an international survey, demonstrating a significant decrease in emergent neurointerventional volume reported by 69% of the responders. We did not find such a decrease in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Remote mentoring is another highly desirable development that will probably soon find its way into clinical routine, partly because one-on-one/in person teaching has become very challenging, if not impossible, during the COVID-19 pandemic. This has led to a dramatic increase in demand for online teaching resources, virtual discussion forums and remote mentoring [ 29 ]. Recent studies have already shown the feasibility and safety of remote live streaming support for emergency neurointerventional procedures, such as mechanical thrombectomy [ 30 ].…”
Section: The Future—where Are We Going?mentioning
confidence: 99%
“…Results of a survey was conducted among neurointerventionalists from all five continents at the beginning of the COVID-19 pandemic showed that 33% of the respondents were in favor of 24/7 availability of remote physician supervision through live stream platforms. This technology was deemed particularly necessary for junior team members undergoing complex procedures without the possibility of supervision by senior partners either due to epidemic mitigation policies or to such members falling ill. 17 …”
Section: Discussionmentioning
confidence: 99%
“…5 Results of a survey was conducted among neurointerventionalists from all five continents at the beginning of the COVID-19 pandemic showed that 33% of the respondents were in favor of 24/7 availability of remote physician supervision through live stream platforms. This technology was deemed particularly necessary for junior team members undergoing complex procedures without the possibility of supervision by senior partners either due to epidemic mitigation policies or to such members falling ill. 17 Remote proctoring for neurointerventional procedures had been first investigated by Bechstein et al in 2019. 18 The authors analyzed 36 thrombectomy procedures performed on an in vitro stroke model using vascular replica by nonsubspecialty trained interventional radiologists either with on-site supervision or with teleproctoring.…”
Section: New Devices and Technologiesmentioning
confidence: 99%